A Novel Breakthrough in Leptospira spp. Mutagenesis: Knockout by Combination of CRISPR/Cas9 and Non-homologous End-Joining Systems - Fernandes, Luis G. V.; Nascimento, Ana L. T. O. (Frontiers in Microbiology, 2022)
Leptospirosis is of general concern as it is a widespread zoonosis caused by pathogenic species of the genus Leptospira, although this genus also includes free-living saprophytic strains. Understanding the pathophysiology of leptospirosis is still in its infancy even after several years, because of the lack of effective genetic tools. The use of the Streptococcus pyogenes CRISPR/Cas9 system and its variations have pushed the leptospirosis research forward, relying on the simplicity of the technique. However, lethality of double-strand breaks (DSB) induced by RNA-guided Cas9 enzyme has limited the generation of knockout mutants. In this work, we demonstrated sustained cell viability after concurrent expression of CRISPR/Cas9 and Mycobacterium tuberculosis non-homologous end-joining components in a single-plasmid strategy in L. biflexa. Scarless mutations resulting in null phenotypes could be observed in most of the colonies recovered, with deletions in the junctional site ranging from 3 to almost 400 bp. After plasmid curing by in vitro passages in medium without antibiotic, selection marker-free and targeted mutants could be recovered. Knockout mutants for LipL32 protein in the pathogen L. interrogans could be obtained using M. smegmatis NHEJ machinery, with deletions ranging from 10 to 345. In conclusion, we have now a powerful genetic tool for generating scarless and markerless knockout mutants for both saprophyte and pathogenic strains of Leptospira.